Numerical study of ball behavior in side-foot soccer kick based on impact dynamic theory - Ishii, H.; Yanagiya, T.; Naito, H.; Katamoto, S.; Maruyama, T. (Journal of Biomechanics, 2009)
This study examined the factors affecting the ball velocity and rotation for side-foot soccer kick using a numerical investigation. Five experienced male university soccer players performed side-foot kicks with various attack angles and impact points using a one-step approach. The kicking motions were captured three-dimensionally by two high-speed cameras at 2500 fps. The theoretical equations of the ball velocity and rotation were derived based on impact dynamic theory. Using the theoretical equations, the relationships of the ball velocity and rotation to the attack angle and impact point were obtained. The validity of the theoretical equations was verified by comparing the theoretical relationships with measurement values. Furthermore, simulations of the ball velocity and rotation were conducted using the theoretical equations. The theoretical relationships were in good agreement with the measurement values. The theoretical results confirmed the previously reported experimental results, and indicated that the impact point is more influential on the ball velocity than the attack angle and the attack angle is more influential on the ball rotation than the impact point. The simulation results indicated the following. The ball velocity produced by impact for all impact patterns is largely affected by the foot velocity immediately before impact but barely affected by the degree of slip between the foot and the ball. The ball rotation produced by an impact with a large attack angle is affected by the foot velocity immediately before impact and the degree of slip between the foot and the ball; however, these factors affect the ball rotation less than the attack angle.